2020
DOI: 10.1016/j.sdentj.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 100 most cited articles on forensic odontology

Abstract: Objectives Bibliometric analysis of best-cited papers brings awareness about the influential publications and trends in the literature on a particular topic. This will help not only the researchers and academicians but also the students for selecting quality landmark articles. With this view in mind a bibliometric analysis was performed to identify the 100 top-cited papers on Forensic Odontology (FO) in the literature. Materials and methods A search was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
2
21
2
2
Order By: Relevance
“…Although the eld of OMFS is very wide, with diverse conditions and treatments, the main nding of this citation analysis indicates that there were only 7 systematic reviews that reached to 100 citations in the eld of OMFS, among the included journals. This is in line with previous studies indicating that less 10% of the published articles reaches up to the status of classic articles [15][16][17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the eld of OMFS is very wide, with diverse conditions and treatments, the main nding of this citation analysis indicates that there were only 7 systematic reviews that reached to 100 citations in the eld of OMFS, among the included journals. This is in line with previous studies indicating that less 10% of the published articles reaches up to the status of classic articles [15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…One interesting factor is that the top ranked systematic reviews are all published after the year 2010, however not surprising since only 14 out of the 100 top cited were published in the decade 2000-2010. One common criticism on citation analysis reports is that the outcome is affected by the impact of time [15]. This was, however, not the case in this report on the eld of OMFS.…”
Section: Discussioncontrasting
confidence: 59%
“…Although the field of OMFS is very wide, with diverse conditions and treatments, the main finding of this citation analysis indicates that there were only 7 systematic reviews that reached to 100 citations in the field of OMFS, among the included journals. This is in line with previous studies indicating that less 10% of the published articles reaches up to the status of classic articles 14-16 .…”
Section: Discussionsupporting
confidence: 93%
“…One interesting factor is that the top ranked systematic reviews are all published after the year 2010, however not surprising since only 14 out of the 100 top cited were published in the decade 2000-2010. One common criticism on citation analysis reports is that the outcome is affected by the impact of time 14 . This was, however, not the case in this report on the field of OMFS.…”
Section: Discussionmentioning
confidence: 99%
“…It was not surprising that the majority of the top cited studies were published between the years of 2007 and 2011 since it has been shown that studies are cited just sparingly with few citations in the first years, followed by a peak of citations just before a study-age of 10 years [ 18 ]. Although the outcome of bibliometric analyses of this kind are criticized for being affected by the impact of time [ 19 ], this is not the case in this study since the bulk of most cited papers are from the years 2007 to 2018 and not from 2000 to 2006.…”
Section: Discussionmentioning
confidence: 97%